Follow-up of Intracranial Aneurysms Treated by Flow Diverters: Evaluation of Parent Artery Patency Using 3D-T1 Gradient Recalled-Echo Imaging with 2-Point Dixon in Combination with 3D-TOF-MRA with Compressed Sensing - Burel, J.; Gerardin, E.; Vannier, M.; Curado, A.; Verdalle-Cazes, M; Magne, N.; Lefebvre, M.; Papagiannaki, C. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: MRA assessment of parent artery patency after flow-diverter placement is complicated by imaging artifacts produced by these devices. The purpose of this study was to assess the accuracy of liver acquisition with volume acceleration-flex technique (LAVA-Flex) MRA in combination with 3D-TOF with HyperSense MRA for the evaluation of parent vessel status after intracranial flow-diverter placement.MATERIALS AND METHODS: Fifty-six patients treated by flow diversion and followed with both DSA and 3T MRA between November 2020 and August 2021 were included. All patients were evaluated for parent artery patency using the same imaging protocol (DSA, noncontrast MRA including 3D-TOF with HyperSense and LAVA-Flex, and contrast-enhanced MRA, including time-resolved imaging of contrast kinetics MRA and delayed contrast-enhanced MRA).RESULTS: With DSA as a criterion standard to evaluate the patency of the parent vessel, noncontrast MRA had a good specificity (0.83) and positive predictive value (0.65), better than contrast-enhanced MRA (0.55 and 0.41, respectively). Both had excellent sensitivity and negative predictive value: noncontrast MRA, 0.93 and 0.97, respectively; contrast-enhanced MRA, 0.93 and 0.96, respectively. Specificity and positive predictive value tended to be lower for patients treated with additional devices than for those treated with flow diverters exclusively and for patients treated with a specific type of flow diverter.CONCLUSIONS: Noncontrast MRA can be used for noninvasive follow-up of intracranial aneurysms treated by flow diverters. The combined use of LAVA-Flex and 3D-TOF with HyperSense sequences allows monitoring the status of the parent artery and aneurysm occlusion.CE-MRAcontrast-enhanced MRAFDflow diverterLAVA-Flexliver acquisition with volume acceleration-flex techniqueNC-MRAnoncontrast MRANPVnegative predictive valuePPVpositive predictive valueTRICKStime-resolved imaging of contrast kineticsVAvertebral artery